Oscillation for Third-Order Nonlinear Differential Equations with Deviating Argument - Miroslav Bartušek; Mariella Cecchi; Zuzana Došlá; Mauro Marini (Abstract and Applied Analysis)
We study necessary and sufficient conditions for the oscillation of the third-order nonlinear ordinary differential equation with damping term and deviating argument x‴(t)+q(t)x′(t)+r(t)f(x(φ(t)))=0. Motivated by the work of Kiguradze (1992), the existence and asymptotic properties of nonoscillatory solutions are investigated in case when the differential operator ℒx=x‴+q(t)x′ is oscillatory.